ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYISIHAN PENGHAPUSAN AKTIVA PRODUKTIF (PPAP) PADA PERBANKAN SYARIAH DI INDONESIA - Iman, Amalia Nurul; Adityawarman, Adityawarman (Diponegoro Journal of Accounting, 2015)
The purpose of this study are to examine the factors that affect the PPAP in Islamic banks. The dependent variable that used in this study was PPAP. Independent variables that used in this studyis the total of Islamic finance (total loans) andcredit risk (non-performing financing). Object (population) in this study is a nationwide company Islamic banking in Indonesia where data that used in this study came from the financial statements of Islamic banks during the period 2011 until 2013. Analyses methods that conducted in this study is descriptive statistics and regression analysis to test each hypothesis. The results showed that the variablethe total of Islamic finance (total loans) showed no significant results on the dependent while the variablecredit risk (non-performing financing) significantly positive effect on the dependent variable (rejected H1, H2 accepted).